2020
DOI: 10.3390/photonics7040104
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Side Wall Roughness Effect on Optical Losses in a Multimode Si3N4 Waveguide Formed on a Quartz Substrate

Abstract: This article presents the results of the study of the influence of the most significant parameters of the side wall roughness of an ultra-thin silicon nitride lightguide layer of multimode integrated optical waveguides with widths of 3 and 8 microns. The choice of the waveguide width was made due to the need to provide multimode operation for telecommunication wavelengths, which is necessary to ensure high integration density. Scattering in waveguide structures was measured by optical frequency domain reflecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Researchers simulated and optimized the bending loss with three-dimensional FDTD technology. Experiments based on advanced bending shows that the bending loss can be reduced to 0.04 dB/90 • [92][93][94][95][96][97][98]. With such low loss, silicon nitride is expected to play an important role in next-generation integrated photonic devices.…”
Section: Si 3 N 4 Waveguidesmentioning
confidence: 99%
“…Researchers simulated and optimized the bending loss with three-dimensional FDTD technology. Experiments based on advanced bending shows that the bending loss can be reduced to 0.04 dB/90 • [92][93][94][95][96][97][98]. With such low loss, silicon nitride is expected to play an important role in next-generation integrated photonic devices.…”
Section: Si 3 N 4 Waveguidesmentioning
confidence: 99%
“…Utilizing bilaterally polished semiconductor quartz wafers with a Ra < 0.5 nm is preferable, deviating from the conventional approach that involves employing a Si substrate and subsequently forming a lower cladding layer using thermal oxide [ 38 ], with Ra < 0.5 nm accounting for less than 2.5% of the fabrication tolerance (around 20 nm), enabling negligible scattering at the strip waveguide interfaces. Additionally, a previous study reported a low optical loss of approximately 0.31 dB/cm for an 8 µm-wide strip; these findings render roughness losses in Si 3 N 4 insignificant [ 39 ]. Moreover, the use of a quartz wafer as a substrate allows for the immediate formation of a Si 3 N 4 waveguide layer, thereby minimizing the introduction of additional defects during production and significantly reducing both the cost and production time [ 40 ].…”
Section: Silicon-nitride Fabricationmentioning
confidence: 99%
“…Quartz wafers are preferred as substrates over Si wafers to optimize performance due to their ability to minimize guided wave leakage and reduce losses [ 36 , 37 ]. To minimize scattering at the strip waveguide interfaces and mitigate roughness losses, it is advised to use semiconductor quartz wafers that have undergone bilateral polishing, resulting in surface roughness (Ra) below 0.5 nm [ 38 , 39 ]. These precise fabrication considerations significantly enhance the performance and reliability of Si3N4-based photonic devices, making them an excellent choice for the proposed 1 × 4 MMI power splitter [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to establish the influence of the surface roughness of the resonator on the value of its Q-factor, a quantitative assessment of the surface roughness of the manufactured samples was performed using a Helios 650 scanning electron microscope. The research of Japanese authors [21,22], as well as previously presented developments [23], was taken as the basis for the development of the technique. The purpose of the method is to study the horizontal edge of an etched element.…”
Section: Evaluation Of the Surface Roughness Of Silicon Resonatorsmentioning
confidence: 99%